Mechanism of Paeoniflorin in the Treatment of Bile Duct Ligation-Induced Cholestatic Liver Injury Using Integrated Metabolomics and Network Pharmacology - Wei, Shizhang; Ma, Xiao; Niu, Ming; Wang, Ruilin; Yang, Tao; Wang, Dan; Wen, Jianxia; Li, Haotian; Zhao, Yanling (Frontiers in Pharmacology, 2020)
Paeoniflorin (PF) is the main active component of Paeonia lactiflora Pall., which is used in the treatment of severe cholestatic hepatitis. However, its biological mechanism in regulating bile acid metabolism and cholestatic liver injury has not been fully revealed. Our study aimed to reveal the mechanism of PF in the treatment of cholestatic liver injury in an in vivo metabolic environment using bioinformatics analysis. The serum of rats with bile duct ligation (BDL)-induced cholestatic liver injury treated with PF was analysed by UHPLC-Q-TOF, and specific metabolites were screened using a metabolomics method. These specific metabolites were further analysed by network pharmacology to identify the upstream signalling pathways and key protein targets. Finally, the key target proteins were verified by immunohistochemistry using cholestatic rat liver tissue. The serum ALT, AST, TBA and TBIL levels, as well as the pathological state of the liver tissues, were significantly improved by PF. Twenty-five specific metabolites and 157 corresponding target proteins were screened for the treatment of cholestatic liver injury by PF. The "PF-target-metabolite" interaction network was constructed, and 5 protein targets (MAP2K1, MAPK1, ILBP, ABCB1 and LTA4H) that may regulate specific metabolites were obtained. The results of immunohistochemistry showed that PF improved the expression of these proteins. The integrated application of multiple bioinformatics methods revealed that PF plays a key role in the treatment of cholestatic liver injury by intervening in important targets related to bile acid metabolism and inflammation.